A formação e ensino de rádio na década de 80: o contributo das rádios piratas - Reis, Ana Isabel (2021)
The 1980s represent a new phase in the Portuguese media landscape and, specifically, in radio. It is the decade of the boom of pirates or free radio. For a generation of journalists, pirates were an inspiration, but they were above all a 'school' in which they discovered or consolidated vocations. Those who started the illegal waves learned from their elders coming from national broadcasters and from the former colonies, anxious to implement the 'radio they dreamed of ' and what they believed to be the 'true' journalism: exempt, outside the institutional or party agenda , who listened to everything and everyone, which was done mainly on the street and live. The 'here and now' and 'nearest' radio, different from the one that existed. The 1980s also marked the professional and academic training of journalists. After the creation of the first university course, journalist training centers were created and radio courses were organized. This study aims to contribute to the characterization of what was the phenomenon of pirate radio in the 1980s in terms of the training of radio journalists. In this sense, a bibliographic review on the subject was made, reports and news of the time were consulted, and professionals were interviewed. The objective is to better understand the contribution of pirate radio stations to the training of radio journalists. It is not intended to know whether it was the formation of a new generation that changed radio journalism or whether it was a new way of doing radio journalism that required other training. Both interconnect and influence the construction of a stage that marked the history of the radio. Radio journalism in the 1980s developed into new parameters. Pirates were 'schools' for a generation that made its name in the newsrooms: the pirate generation.